Ответы и объяснения

2013-12-21T15:19:52+00:00
Решение: 
( х+5)^2 = Х2 +10Х+25
(N-4)(N+4) = n^2 -4^2
(Х -3)^3 = x^3- 9x^2+3x* 9^2-27
(6y - 9t)(9t+6y)= 36y^2 - 81t^2 
2)
36y^2 - 25 = (6y - 5)(6y+5)
64х^2 - 32xy + 4y = (8x - 2y)
3)
(x - 4)^2  - x^2 - 8 = x^2 -8+16 -x^2 - 8 = 0

( 5x - 8)^2- 9x^2 = 0
25x^2 - 80 + 64 - 9x^2 = 0
16 x^2 -16 = 0
16x^2 = 16
x^2 = 1
x = 1
4)
(x-5)(x+5) - (x+1)(x-3) + (x-2)^2  = x^2 - 25 - x^2 - 3x +x -3 + x^2 - 4x + 4= x^2 - 6x - 24
подставляем
(-3)^2 - 6 (-3) - 24 = 9+18-24 = 3